Nazarov Uncertainty Principle for Certain Lie Groups (Journal of Informatics and Mathematical Sciences, 2025)
Nazarov uncertainty principle is established for the Fourier transform and the continuous modulated shearlet transform on the groups of the form \(\mathbb{R}^n × K\), where \(K\) is a locally compact group. As special cases, Nazarov uncertainty principle follows for the Gabor transform, the shearlet transform and the wavelet transform on these groups.